Copy Number Variation of Satellite III (1q12) in Patients With Schizophrenia - Ershova, Elizaveta S.; Agafonova, Oksana N.; Zakharova, Natalia V.; Bravve, Lidia V.; Jestkova, Elizaveta M.; Golimbet, Vera E.; Lezheiko, Tatiana V.; Morozova, Anna Y.; Martynov, Andrey V.; Veiko, Roman V.; Umriukhin, Pavel E.; Kostyuk, Georgiy P.; et al. (Frontiers in Genetics, 2019)
Introduction. It was shown that CNVs of human satellite III (1q12) fragment (f-SatIII) reflects the human cells response to stress of different nature and intensity. Patients with schizophrenia (SZ) experience chronic stress. The major research question: What is the f-SatIII CNVs in human leukocyte as a function of SZ? Materials and Methods. Biotinylated pUC1.77 probe was used for f-SatIII quantitation in leukocyte DNA by the non-radioactive quantitative hybridization for SZ patients (N = 840) and healthy control (HC, N=401). SZ-sample included four groups. Two groups: first-episode drug-naïve patients (SZ(M-)) and medicated patients (SZ(M+)). The medical history of these patients did not contain reliable confirmed information about fetal hypoxia and obstetric complications (H/OCs). Two other groups: medicated patients with documented H/OCs (hypoxia group (H-SZ(M+)) and medicated patients with documented absence of H/OCs (non-hypoxia group (NH-SZ(M+)). The content of f-SatIII was also determined in eight post-mortem brain tissues of one SZ patient. Results. f-SatIII in human leukocyte varies between 5.7 to 44 pg/ng DNA. f-SatIII CNVs in SZ patients depends on the patient’s history of H/OCs. f-SatIII CN in NH-SZ(M+)-group was significantly reduced compared to H-SZ(M+)-group and HC-group (p < 10-30). f-SatIII CN in SZ patients negatively correlated with the index reflecting the seriousness of the disease (PANSS). Antipsychotic therapy increases f-SatIII CN in the untreated SZ patients with a low content of the repeat and reduces the f-SatIII CN in SZ patients with high content of the repeat. In general, the SZ (M+) and SZ (M-) groups do not differ in the content of f-SatIII, but significantly differ from the HC-group by lower values of the repeat content. f-SatIII CN in the eight regions of the brain of the SZ patient varies significantly. Conclusion. The content of f-SatIII repeat in leukocytes of the most patients with schizophrenia is significantly reduced compared to the healthy control. Two hypotheses were put forward: (1) the low content of the repeat is a genetic feature of schizophrenia; and/or (2) the genomes of the schizophrenia patients respond to chronic oxidative stress reducing the repeats copies number.